Comparative Study of Digital and Conventional Media in Elementary School Fraction Learning: A Systematic Literature Review - Emanuel Hosa Kurnia Adi; Akhmad Faisal Hidayat (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Understanding fractions is an essential competence for elementary school students, yet its abstract nature often leads to misconceptions and low learning outcomes. In the era of digital transformation, educators are faced with a choice between using interactive digital media or conventional media based on manipulative objects. This study aims to synthesize and compare the effectiveness of these two media categories in improving mathematics learning outcomes for fraction materials in elementary schools. This research adopts a Systematic Literature Review (SLR) method, analyzing 20 primary literatures published between 2018 and 2025. Data were identified using Publish or Perish software and subjected to comparative analysis. The findings indicate that digital media (53% dominance) is highly effective as a cognitive accelerator that enhances extrinsic motivation and the speed of solving procedural problems through dynamic visualization. Meanwhile, conventional media (47%) remains crucial as a